Doxycycline sensitivity in multidrug resistant Acinetobacter baumanii isolates from blood - Khan, Fatima; Siddiqui, Naushaba; Shukla, Indu; Shujatullah, Fatima (Annals of Pathology and Laboratory Medicine, 2014)
Background: Acinetobacter species has become a leading cause of blood stream infection in health care setting. Acinetobacter species possess a wide array of Î²-lactamases that hydrolyze and confer resistance to penicillins, cephalosporins and carbepenems. Doxycycline, a semisynthetic tetracycline, has effective antibacterial effect on multidrug resistant Acinetobacter species. Methods:Â Total numbers of 13,880 samples were received in 5 years for blood culture in brain heart infusion broth. Antimicrobial susceptibility testing was done on Mueller Hintonâ€™s agar by Kirby Bauer Disc diffusion method as per the Clinical and Laboratory Standards Institute (CLSI) guidelines for the following antimicrobials: cefotaxime 30Âµg, ceftriaxone 30Âµg, cefoperazone 75Âµg, cefipime 30Âµg, cefoperazone+sulbactum 75/75 Âµg, gentamicin 10Âµg, amikacin 30Âµg, netilmicin 30Âµg, tobramycin 10Âµg ,ciprofloxacin 5Âµg, piperacillin+tazobactum 100/10 Âµg , Imipenem 10Âµg and doxycycline 30Âµg. Isolates resistant to atleast three drugs belonging to three different groups were considered to be multidrug resistant (MDR). Results: One hundred and fifty one isolates were identified as Acinetobacter baumanii. Majority of the isolates 101(66.88%) were from the patients between 0-10 years of age. 45% of the isolates were found to be multidrug resistant. Barring imipenem, doxycycline was found to have the best spectrum of activity with just 48.34% (73 isolates) resistance Conclusion: Rational and appropriate use of antimicrobial agents is of paramount importance to minimize the risk of resistant organism. Doxycycline can be used as an effective therapeutic agent in multidrug resistant Acinetobacter baumanii. Â